The relationship between gratitude and social support with psychological well-being among university students - Faridah Ainur Rohmah; Faliza Alfidyah Ibzan (Universitas Ahmad Dahlan, 2025)
Many university students encounter academic challenges that may lead to elevated levels of stress and anxiety, potentially indicating low psychological well-being. This study aims to examine the relationship between gratitude and social support with psychological well-being among university students. A total of 120 participants were selected using a cluster random sampling technique. The study employed a correlational quantitative research design, utilizing three standardized instruments: the Gratitude Scale, the Social Support Scale, and the Psychological Well-Being Scale. Data were analyzed using multiple linear regression with SPSS version 27.0. The primary hypothesis testing revealed a significant correlation, with a coefficient of determination R = 0.795 and p = 0.000 (p < 0.01), indicating a strong and statistically significant relationship between gratitude, social support, and psychological well-being. For the first sub-hypothesis, the partial correlation coefficient was 0.327 with a significance level of p = 0.000 (p < 0.01) and a beta value of 0.380, suggesting a significant positive relationship between gratitude and psychological well-being. The second sub-hypothesis showed a partial correlation coefficient of 0.380, a significance level of p = 0.000 (p < 0.01), and a beta value of 0.451, indicating a significant positive relationship between social support and psychological well-being. Based on these findings, it can be concluded that gratitude and social support collectively contribute to 63.2% of the variance in psychological well-being. These results underscore the importance of fostering gratitude and enhancing social support among university students to promote greater psychological well-being.